Striking up with the in crowd: When option markets and insiders agree - Gilstrap, Collin; Petkevich, Alex; Teterin, Pavel (Journal of Banking & Finance, 2020)
We study whether the trading behavior of corporate insiders provides additional information to the market, after controlling for the public information integrated by sophisticated investors. First, we establish that insiders and option market participants trade in the same direction on average. Second, we show that insidertrading is relatively more informed when the option market sentiment is positive. The marginal information content of insider trades is higher for firms with higher levels of information asymmetry and during time periods when future economic conditions are less certain.